Gut microbial characteristical comparison reveals potential anti-aging function of Dubosiella newyorkensis in mice - Liu, Tian-hao; Wang, Juan; Zhang, Chen-yang; Zhao, Lin; Sheng, Ying-yue; Tao, Guo-shui; Xue, Yu-zheng (Frontiers in Endocrinology, 2023)
Previous study has indicated Dubosiella newyorkensis may act as a potential probiotic in age-related diseases. However, its detailed role in aging has not yet been promulgated. This study aimed to explore the potential anti-aging role of Dubosiella newyorkensis by comparing the anti-aging effect of resveratrol in young and old mice. Measurement of intestinal aging-related factors in colon and serum, and vascular endothelial function-related factors in serum were performed by enzyme-linked immunosorbent assay (ELISA). Gut microbial analysis of intestinal contents were identified by 16S rRNA gene sequencing. The effect of Dubosiella newyorkensis on reducing malondialdehyde (MDA) and increasing superoxide dismutase (SOD) in aged mice were greater than that of resveratrol. While the effect of Dubosiella newyorkensis on nitric oxide (NO) level was less than that of resveratrol, the reduction of vascular endothelial growth factor (VEGF) and pentosidine (PTD) was better than that of resveratrol in young mice. In young mice, Dubosiella newyorkensis promoted an increase in the beneficial genus Lactobacillus, Bifidobacterium and Ileibacterium less effectively as compared with resveratrol treatment. In aged mice, Dubosiella newyorkensis promoted the increase of Bifidobacterium, Ileibacterium less effectively than resveratrol, and promoted the increase of Akkermansia, Staphylococcus, Verrucomicrobiota expression better as compared with resveratrol treatment. Both young and old mice showed the same results for the remaining markers, including changes in gut microbial composition and predictions of function. Dubosiella newyorkensis has similar anti-aging functions with resveratrol. Dubosiella newyorkensis may even be more effective than resveratrol in reducing oxidative stress, improving vascular endothelial function, and redistributing gut microbiota. The research provides an innovative strategy of Dubosiella newyorkensis to improve aging.